2014
DOI: 10.5195/cajgh.2014.140
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Gestational Diabetes and Hypertension Among Antenatal Women in Rural West India

Abstract: BackgroundHypertension and gestational diabetes are among the leading causes of maternal and perinatal mortality, especially in rural areas of developing countries with meager health facilities. With early diagnosis and timely treatment, these adverse events can be decreased. The primary aim of this study was to implement a screening program for gestational diabetes and hypertension, and to assess risk factors associated with these conditions among antenatal women in the rural area of the Gujarat province in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…In another study past history of abortion as a risk factor of GDM was evaluated and it reported that out of 723 GDM diagnosed females, 23.7% had history of abortions and it was a significant association on the basis of O'Sullivan's criteria (ACOG guidelines) but overall it was insignificant association (Somani et al, 2012). Hypertension (HTN) was another significant risk factor in our results and our results were comparable to reported literature as one of the study from China and rural west India reported HTN as a significant risk factor of GDM (Dave et al, 2014) and the odd ratio of increased systolic blood pressure was 1.31 (P<0.001), this result was consistent with odd ratio of HTN thin our study which was 1.93 (P=0.028) (Leng et al, 2015). In another literature it was reported that about 8% of pregnancies are accompanied by preeclampsia and gestational hypertension and it is observed that such females develop insulin resistance during gestation period resulting in GDM (Feig et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…In another study past history of abortion as a risk factor of GDM was evaluated and it reported that out of 723 GDM diagnosed females, 23.7% had history of abortions and it was a significant association on the basis of O'Sullivan's criteria (ACOG guidelines) but overall it was insignificant association (Somani et al, 2012). Hypertension (HTN) was another significant risk factor in our results and our results were comparable to reported literature as one of the study from China and rural west India reported HTN as a significant risk factor of GDM (Dave et al, 2014) and the odd ratio of increased systolic blood pressure was 1.31 (P<0.001), this result was consistent with odd ratio of HTN thin our study which was 1.93 (P=0.028) (Leng et al, 2015). In another literature it was reported that about 8% of pregnancies are accompanied by preeclampsia and gestational hypertension and it is observed that such females develop insulin resistance during gestation period resulting in GDM (Feig et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Two hospital-based studies carried out in Wardha (Maharashtra)[ 61 ] and Rohtak (Haryana)[ 62 ] showed GDM prevalence significantly associated with higher education when identified using the WHO and American Diabetes Association (ADA) criteria, respectively. However, other community-based cross-sectional studies carried out in Punjab,[ 63 ] Gujarat,[ 64 ] and Kashmir[ 65 ] invariably showed positive association between GDM and illiteracy, irrespective of the criteria used. In another community-based study,[ 64 ] the authors found the prevalence of GDM positively associated with nonworking group when diagnosed using ADA criteria, though the association was statistically nonsignificant (OR = 1.14; 95% CI: 0.20–6.35; P = 0.28).…”
Section: R Esults and Discussionmentioning
confidence: 97%
“…However, other community-based cross-sectional studies carried out in Punjab,[ 63 ] Gujarat,[ 64 ] and Kashmir[ 65 ] invariably showed positive association between GDM and illiteracy, irrespective of the criteria used. In another community-based study,[ 64 ] the authors found the prevalence of GDM positively associated with nonworking group when diagnosed using ADA criteria, though the association was statistically nonsignificant (OR = 1.14; 95% CI: 0.20–6.35; P = 0.28). However, in another retrospective matched case–control study carried out in Malaysia, the authors found a significant association between GDM and occupation (χ 2 = 4.01; P = 0.045).…”
Section: R Esults and Discussionmentioning
confidence: 97%
“…Type 2 diabetes is a chronic disease, which presents a significant burden on health services in many countries, 1 , 2 including low income nations such as Afghanistan 3 and Bangladesh, 4 and middle income countries such as Kazakhstan 5 and India. 6 Type 2 diabetes is a metabolic disorder characterized by a deficit in the production or release of insulin, increasing glucose levels in plasma. 7 , 8 This chronic disease and its complications are a major cause of morbidity and mortality in Mexico, 9 with over 400,000 new cases reported in Mexico each year.…”
mentioning
confidence: 99%